Desenvolvimento de uma toolbox para aplicação de inteligência computacional em sistemas de controle clássico - Dantas, Emmanuel Ramon Marques (Universidade Federal Rural do Semi-Árido, 2013)
A new tool based on the use of computational intelligence applied in control systems is presented. This type of application has attracted the interest of researchers due the advantages in relation to others methods for controlling settings, especially when the system has a complex dynamics to be adjusted by traditional methods. The proposed computational tool GACT (Genetic Algorithm Control Tool) was developed to work as a Toolbox of MATLAB® software for use in control systems and is based on the joint application of Genetic Algorithms (GA) and the classical control theory. The GACT based on the advancement of the operating systems that are no longer fully handled by command lines, and now have an interactive graphical user interface. That is, the referred Toolbox allows the implementation of an intelligent control system in a way more simplified and interactive. The graphical user interface (GUI) was designed using the software GUIDE, integrated with MATLAB® in order to connect with the source code and block diagrams of the system to be controlled at the SIMULINK®
Development of a toolbox for application of computational intelligence in classic control systems
Keywords: Computational Intelligence, Genetic Algorithm, Control Systems, Graphical User Interface; Inteligência computacional; Algoritmo genético; Sistemas de controle; Interface gráfica; ENGENHARIAS::ENGENHARIA ELETRICA